The limit load calculations for pipelines with axial complex-shaped defects - Bogdan, A.V.; Lokhman, I.V.; Ageev, S.M.; Orynyak, I.V. (Проблемы прочности, 2009)
Based on the analytical model for the plastic limit state, a numerical procedure for estimating the remaining strength of a complex-shaped defect has been developed. Comparison of the calculation results obtained by the proposed procedure with the experimental data and the calculation results obtained by other methods showed its efficiency.